The genus Moenchia (Caryophyllacae) in Turkey_x000D_ - (:unkn) unknown (My University, 2021)
ctA new identification key, full descriptions, and distribution records based on various herbaria of TurkishMoenchia are given in this study. Detailed and comparative descriptions of the studied species have been prepared.Also, a new species, Moenchia akmanii M.Keskin sp. nov., is described as for science. The new species ismorphologically similar to M. graeca that is but differs by long stems, different leaves, non-flowering shoots, 3-nervedsepals, mauve anthers, etc. The new identification key has been created to distinguish taxa distributed in Turkey.

Bu çalışmada, Türkiye'de yetişen Moenchia cinsine ait yeni teşhis anahtarı, betimlemeler ve dağılımlar çeşitli_x000D_ herbarium numunelerine dayanılarak verilmiştir. İncelenen türlere ait detaylı ve karşılaştırmalı betimlemeler_x000D_ hazırlanmıştır. Ayrıca Moenchia akmanii M.Keskin sp. nov. adıyla bilim dünyasına yeni bir tür tanıtılmıştır. Bu yeni_x000D_ tür, morfolojik olarak M. graeca türüne benzemekle beraber ondan uzun gövdesi, farklı yaprakları, çiçeksiz sürgünleri,_x000D_ 3-damarlı sepalleri, mor anterleri vb. karakterleri ile ayrılmaktadır. Türkiye'de yayılış gösteren taksonları ayırt etmek_x000D_ için yeni teşhis anahtarı oluşturulmuştur._x000D_
Türkiye'deki Moenchia (Caryophyllacae) cinsi